Assessment of a predictability index for humpback whales' supergroups occurrences in the Southern Benguela - De Souza, Cayla (Department of Oceanography, 2026)
The highly productive Benguela upwelling system in the south-eastern Atlantic Ocean plays a crucial role in ocean productivity and nutrient cycling. Its termination at the tip of Africa creates a distinct ecological niche, fostering a diverse marine ecosystem. Since 2011, unprecedented aggregations of humpback whales (Megaptera novaeangliae) have been observed in the Southern Benguela. It has been proposed that positive chlorophyll anomalies and reduced outward transport serve as potential indices for predicting the formation of humpback whale super-groups with a lead time of at least one month (Dey, S.P., Vichi, M., Fearon, G., Seyboth, E., Findlay, K.P., Meynecke, J.O., de Bie, J., Lee, S.B., Samanta, S., Barraqueta, J.L.M. and Roychoudhury, A.N., 2021. Oceanographic anomalies coinciding with humpback whale super-group occurrences in the Southern Benguela. Scientific Reports, 11(1), p.20896.). By utilizing an extended time series of satellite data and a different ocean model output (CMEMS) until 2022, the study aims to validate the proposed indices and deepen our understanding of the oceanographic preconditioning and patterns associated with super-group formations. The Dey et al. (2021) index has been compared with new sightings from various formal and informal sources. There are notable discrepancies between the two Ocean Models; the CMEMS simulation demonstrates a more zonal orientation of the Good Hope Jet. Additionally, the CMEMS simulation presents a greater mean outward transport during 2011. Consistent observations of humpback whale super-groups well into the summer season despite negative chlorophyll and retention indices suggest a more intricate change in oceanographic conditions within the focus region. Notable changes in eddy kinetic energy and outward transport since 2017 suggest an increased variability in resource availability within the environment. The aggregations of humpback whale super- groups since 2017 occurred at smaller spatial scales near the Cape Peninsula upwelling cell. The rising trend of humpback whale super-groups within the Southern Benguela, particularly in the Cape Peninsula and Cape Columbine region, emphasizes the importance of these regions as critical feeding grounds.